(untitled) (Archives of Criminology, 1986)
Both the anthropological school of Lombroso, established in the late half of the 19th century, and the sociological school established by Ferri and other criminologists ( Liszt, Prins, van Hammel, Tarde) met with a keen interest in Poland. However, the anthropological school was criticized, as it was the case in other countries too, both by the classical school of penal law, and from the sociological point of view. A critical analysis of the views of Lombroso and his successors was made by the leading representative of the classical school of penal law in Poland in those days Krzymuski who postulated that recognition of the individual’s free will to be condition of his penal liability, Krzymuski opposed free will to be conception of a born criminal propagated by Lombroso. Lombroso’s theory was also criticized by Krzywicki, a sociologist and anthropologist who considered the former’s approach towards the conditions of crime to be too narrow, leaving out of account those resulting from the social and economic conditions. On the other hand, Polish criminologists considered it to be Lombroso’s unquestionable merit that he had called attention to the necessity of studying the offender’s personality, and in this way initiated the modern criminology. Opinions of various sociological schools were discussed in the Polish literature and accepted by the majority of authors starting from the close of the 19th century. In particular, the most accepted one was the opinion that offence is a result of both individual and social factors, and the aim of punishment meted out by the court should be not only to deter. the perpetrator from committing offences, but also to reeducate him. Due to the fact that in the 19th-centuiy judicial practice the sentence depended on the extent of damage caused by the offender, it was emphasized in the Polish literature that punishment should take into consideration also the offender’s individual features, as it is only then that it can fulfil its tasks (Stebelski). With the accepted division of offenders into professional and causal, the fact was stressed that - if the offender reveals a tendency to relapse into crime- the measures the society applies towards him should be more drastic since the society has to defend itself against incorrigible criminals in an effective way. Instead, more lenient measures should be applied towards causal offenders, such measures being sufficient for their reeducation. In the period between the two world wars, criminology in Poland became a separate branch and extended its range; the establishment of the Polish Criminological Society in 1921 and of the Department of Criminology at the Free Polish University in 1922, later (I932) transformed into the Criminological Institute, contributed to this situation. The Polish criminology of that period faced the task of studying and defining in detail the basic factors of crime: individual (endogenous) and social (exogenous). This was related to the necessity to learn about the sources of crime with the aim of its effective control by means of preparing a Penal Code and properly shaping the criminal policy (Wróblewski). When studying the individual factors of crime, particular attention was paid to the psychopathic personality. Criminal psychopaths were believed to suffer from a pathological moral defect resulting from their underdevelopment in the sphere of emotions. It was stated that psychopaths who committed an offence should not be recognized as mentally irresponsible (Nelken). Psychopathy cannot be treated psychiatrically; on the other hand, intensified resocialization of the offender is necessary here, conditions for this treatment created during his prison term. At the same time, an adequate segregation of prisoners should be applied based on the psychopathological criterion (Łuniewski). The science of the offender’s personality was called criminal biology; it dealt with the physical and mental structure of the offender. Criminal biology was to make use of the general anthropological, psychological and psychiatric data as well as those gathered by means of other clinical methods. Aimed at gathering comprehensive data concerning the whole of the offender’s mental and physical properties, criminal biology should not confine itself to a mere specification of his various traits: it should also study their origin, methodically examining the development of these properties in the milieu in which the offender’s personality was formed. Thus the criminal-biological research must be made from the psychological and medical as well as sociological points of view. Particular importance was attached to detailed environmental research in the study of juvenile delinquents (Batawia). In the early Thirties, the Ministry of Justice initiated criminological- biological research in prisons. The research was carried out by special commissions with the use of a specially prepared comprehensive questionnaire . The greatest part was played by psychiatric and psychological examination. The criminal-biological research in prisons was interrupted by the outbreak of the war. In connection with the criminogenic role of alcoholism, criminologists spoke for a considerable reduction of production and sale of spirits. Moreover, an opinion was expressed that a commission of an offence in the state of a normal (the so-called physiological) intoxication should not result in the recognition of the offender as mentally irresponsible. Only pathological intoxication may be considered from the point of view of irrespossibility. The offender should not avail himself of his intoxication as a mitigating circumstance (Nelken). The scientists opposed the introduction of compulsory sterilization which was to be applied toward persons whose children could inherit serious pathological traits from them. The opposition had both scientific and humanistic grounds (Łuniewski, Nelken). Compulsory sterilization was not introduced. The main trend of the Polish criminology in the period between the wars corresponded with the sociological school which took into account the relationship between the endogenous (biological) and the exogenous (social) factors in the origins of crime. A vast majority of Polish criminologists opposed the conception of a “born criminal” put forward by Lombroso. Some of the Polish scholars of the period between the wars who used the term “criminal anthropology” (e.g. Rabinowicz), emphasized the evolution of this science which differed from the Lombroso’s doctrine, and postulated the social milieu as a factor be largely taken into consideration in the studies on the causes of crime. In the Polish criminology of those days, the stress was laid principally on criminal biology due to the fact that the internal factor is usually less conspicuous and more difficult to prove than the external one in the etiology of crime. It was emphasized that not all of persons who found themselves in unfavourable social conditions turned offenders (Neymark, Lemkin); therefore, the biological (somato psychological) factor determines the individual’s moral resistance to the unfavourable external conditions. On the other hand, also the social factor, in addition to the biological one, was included in the causes of crime, due to the considerable impact of living conditions on the human mind. The opinion was that - though the etiology of an offence is usually determined by a combination of the external and internal factors - in each case one should attempt to find out which of these factors prevailed in the origin of a given act; this should also be taken into account in the criminological prognosis. In general, the chance for correction is smaller in the case of an offender of the endogenous type who requires a more thorough and longer resocialization as compared with one of the exogenous type; this should be taken into account by the court when meting out punishment (Rabinowicz, Lemkin). The Polish Penal Code of 1932 (in force till 1969) was an expression of the compromise between the classical school of penal law and the sociological school. In the code, many legal structures included in the General Part were formulated in accordance with the achievements of the science of penal law in its classical form; this concerns particularly the definition or the essence of crime and the principles of liability including that of subjectivism as responsibility for a culpable act. A compromising character was given in the code to meting out punishment which was conditioned not only by the weight of the offence according to the classical principle of retribution and deterrence, but also by the offender’s personality and the life he had led hitherto according to the instructions of the sociological school (Art. 54). The discussed code did not adopt from the Italian positivism the so-called ante-criminal prevention, i.e.. the application of sanctions towards an individual who has not committed any prohibited act yet. Also indeterminate sentences were not adopted in the Code in relation to penalties and not protective measures, as this would be contradictory to the principle of individualization of punishment. Under the influence of the sociological school the Code contained of a possibility of suspension of ęxceution of the penalty, and of its extraordinary rnitigation, as well as the release from prison before the expiration of term (separately regulated by the law of 1927-) and a possibility to mete out a more severe penalty in the case of recidivists. In addition to the medical security measures, which consisted in the commitment of the offender to a mental hospital and which the court could apply towards the persons guilty of acts committed in the state of mental irresponsibility or decreased responsibility, the code introduced - basing on the postulates of the sociological school-isolating security measures applied towards the offenders whose acts were connected with reluctance to work, and towards recidivists and professional as well as habitual criminals if their staying at liberty endangered the legal order. The isolating security measures were applied together with the penalty (not instead of it), the necessity of their application connected with the ‘’ state of danger", i.e. the perpetrator’s probability of commission of further offences; in the criminological literature, subjective and state of objective criteria of the danger were distinguished (Strasman). According to Art. 84 of the Penal Code, offenders of this type were committed to a special institution for at least 5 years, and the court decided after the termination of each such period whether it was necessary to prolong the commitment for the next five years. In the Penal Code of 1932, also the measures applied towards juvenile delinquents were divided into educational measures on the one hand, and commitment to a corrective institution on the other hand, depending on the juvenile’s age and of his possible discernment or lack there of when committing the forbiden act.